GEOCHRONOLOGY OF THE NEOGENE-QUATERNARY DACITIC VOLCANISM IN THE NORTHWESTERN LESSER CAUCASUS (GEORGIA) - Lebedev V.A.; Chernyshev I.V.; Arakelyants M.M.; Gol'tsman Yu.V.; Dudauri O.Z.; Vashakidze G.T. (My University, 2004)
The isotopic geochronology of a representative collection of moderately acidic volcanics from the Javakheti neovolcanic area in the northwest of the Lesser Caucasus (Georgia) is studied using the K–Ar and Rb–Sr methods. Three discrete stages of the regional volcanic activity took place in that area during the late Miocene (about 8–7 Ma), Pliocene (4–2 Ma), and Quaternary (800–about 50 ka). Moderately acidic volcanic rocks were most characteristic of the first and third stages, whereas basalts with subordinate rhyolite–dacitic lavas were typical of the second one. The K–Ar dates evidence for intermittent formation of the Javakheti dacites formerly attributed altogether to one Goderdzi Formation. Pyroclastic units and intraformational dacitic flows exposed in the Kura River valley were formed in the late Miocene (7–8 Ma). The extrusive domes of the Amiranisgora and Chikiani volcanoes emerged at about 3 Ma. Dacitic lavas of the Javakheti Ridge were erupted probably in the Late Pliocene (about 2 Ma). Dacitic volcanism of the Samsari Ridge that commenced at about 800 ka had three discrete phases responsible for the formation of the “western range” volcanoes (800–700 ka), the Samsari caldera and other volcanoes of the main ridge (300–200 ka), and parasitic volcanoes and hyalodacitic lava flows (later than 50 ka). The volcanic activity in the Samsari Ridge continued up to the late Pleistocene or, probably, to the Holocene. Accordingly, this area of the Javakheti region is potentially hazardous with respect to volcanism reactivation. It was found out that plagioclase phenocrysts of the Javakheti dacitic lavas contain the 40Ar excess and differ in initial Sr and Nd isotopic ratios from the rock groundmass. These peculiarities previously noted for Quaternary lavas in other Caucasian volcanic centers appear to be also characteristic of Pliocene rocks. It is confirmed that the K–Ar dating of young volcanics, when applied to their groundmass, yields the most reliable results.
Keywords: Quaternary; Neogene; Cenozoic::Quaternary; Cenozoic::Neogene; Кайнозой::Неоген; Кайнозой::Четвертичная